Աղբյուրների ժողովրդական պաշտամունքի հետ կապուած եկեղեցական արարողութիւններ - Նարեկ Տ․ Վարդապետ Ավագյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье представлены народные обряды орошения полей в целях защиты от вредителей и зараз, взятые особым ритуалом из считающихся священными источников. Вода, принесенная из священных источников, в народном понимании носила в себе силу чуда, случившегося на территории ключа или на месте, где находятся мощи святого. The article presents folk ceremonies to protect against various infections and pests by sprinkling fi elds with water taken with a special ritual from springs considered to be sacred․ The water brought from sacred springs was popularly perceived to have the power of the miracle performed at the source of that spring or of the relic of the saint buried there.
Keywords: Practical Theology; Religion; Cults; Christianity; Liturgy and Ritual